Static Descriptions of Three-Phase, Three-Sensitive Element Transmitter - Anarboev Mukhiddin Almanovich; Tulakov Jahangir Turaqul ugli (Genius Journals, 2022)
The article analyzes the structural principles of the converters that convert the value of the primary currents in the control and control of the reactive power of the power supply system to the output signal in the form of voltage. The dependence of the appearance of the output voltage on the different parameters of the distributed parametric, three-phase, three-sensing element converter has been studied.
Keywords: Reactive power; suitable sensing element; electromagnetic current; magnetic resistance